Risk assessment of N‐nitrosamines in food. (28th March 2023) - ,; Schrenk, Dieter; Bignami, Margherita; Bodin, Laurent; Chipman, James Kevin; del Mazo, Jesús; Hogstrand, Christer; (Ron) Hoogenboom, Laurentius; Leblanc, Jean‐Charles; Nebbia, Carlo Stefano; Nielsen, Elsa; Ntzani, Evangelia; et al.
Abstract: EFSA was asked for a scientific opinion on the risks to public health related to the presence of N ‐nitrosamines ( N ‐NAs) in food. The risk assessment was confined to those 10 carcinogenic N ‐NAs occurring in food (TCNAs), i.e. NDMA, NMEA, NDEA, NDPA, NDBA, NMA, NSAR, NMOR, NPIP and NPYR. N ‐NAs are genotoxic and induce liver tumours in rodents. The in vivo data available to derive potency factors are limited, and therefore, equal potency of TCNAs was assumed. The lower confidence limit of the benchmark dose at 10% (BMDL10 ) was 10 μg/kg body weight (bw) per day, derived from the incidence of rat liver tumours (benign and malignant) induced by NDEA and used in a margin of exposure (MOE) approach. Analytical results on the occurrence of N ‐NAs were extracted from the EFSA occurrence database (n = 2, 817) and the literature (n = 4, 003). Occurrence data were available for five food categories across TCNAs. Dietary exposure was assessed for two scenarios, excluding (scenario 1) and including (scenario 2) cooked unprocessed meat and fish. TCNAs exposure ranged from 0 to 208.9 ng/kg bw per day across surveys, age groups and scenarios. 'Meat and meat products' is the main food category contributing to TCNA exposure. MOEs ranged from 3, 337 to 48 at the P95 exposure excluding some infant surveys with P95 exposure equal to zero. Two major uncertainties were (i) the high number of left censored data and (ii) the lack of data on important food categories. The CONTAM Panel concluded that the MOE for TCNAs at the P95 exposure is highly likely (98–100% certain) to be less than 10, 000 for all age groups, which raises a health concern.